THE INFLUENCE OF AGE AND EDUCATION ON IMPLEMENTATION OF BREAST SELF EXAMINATION (BREAST) IN PEMALANG DISTRICT IN 2021 - Elqy Mei Zumaro (Lppm Unan, 2022)
Background: Cancer is one of the leading causes of death worldwide, it is estimated that as many as 9 million people died from cancer in 2015 and 11.4 million died in 2030, more than 70% of all cancer deaths in 2005 occurred in low-income countries low and medium (Parkway Cancer Centre, 2011). An estimated 50% of breast cancer patients in Indonesia come to have their cancer checked at an advanced stage. Early detection of breast cancer is a good first step to find out the presence of breast cancer as early as possible, namely by breast self-examination (BSE). the purpose of this study was to determine the effectiveness of breast self-examination at (Case Study of Kabunan Health Center) Pemalang in 2021. Method: This research is an analytic survey research with a cross sectional approach. The population and sample in this study were all women of childbearing age (WUS) who visited the Melati posyandu in Asemdoyong village in September 2021 with a total of 36 people. Results: The results showed that there was an effect of age on the application of BSE (p 0.013), there was an influence of education on BSE (p 0.010).